Exhaled nitric oxide and carbon monoxide in lung transplanted patients. Issue 9 (September 2015) - Cameli, P.; Bargagli, E.; Fossi, A.; Bennett, D.; Voltolini, L.; Refini, R.M.; Gotti, G.; Rottoli, P.
Abstract Background Exhaled nitric oxide (eNO) and carbon monoxide (eCO) are markers of pulmonary inflammation associated with acute graft rejection and lung infections in lung transplant (LTX) recipients. Regarding eNO and eCO levels in LTX patients affected by bronchiolitis obliterans syndrome (BOS), published data are discordant. Objectives We aim to evaluate eNO at multiple flows, alveolar concentration of nitric oxide (CalvNO), maximum conducting airway wall flux (J'awNO) and eCO levels in LTX patients to assess the potential role of these parameters in BOS evaluation. Methods Fractional exhaled nitric oxide (FeNO), CalvNO and J'awNO were analysed in 30 healthy subjects and 27 stable LTX patients (12 BOS patients). Pulmonary function tests were performed after eNO and eCO assessment. Receiver operating characteristic (ROC) curves were conducted to evaluate diagnostic accuracy for BOS of eNO parameters. Results LTX patients reported higher values of FeNO at flow rates of 50 (p < 0.01), 150 (p < 0.05), 350 ml/s (p < 0.001), and CalvNO (p < 0.0001) than healthy controls. BOS patients showed higher FeNO at flow rates of 150 (p < 0.05) and 350 ml/s (p < 0.01) and CalvNO (p < 0.001) than non-BOS patients. CalvNO reported a remarkable diagnostic accuracy for BOS (AUC: 0.82). There were no significant differences of eCO levels between LTX patients and healthy controls. Conclusion LTX patients affected by BOS showed higher levels of FeNO 150 and 350, and CalvNO than non-BOS LTX patients, probably due to chronic airway inflammation and fibrotic remodelling. CalvNO may be a potential biomarker of BOS in LTX patients.